PEMANFAATAN LAHAN SAWAH SESUDAH PADI DENGAN TATA TANAM UNTUK PENINGKATAN PERTUMBUHAN DAN PRODUKSI DUA VARIETAS WIJEN (Sesamun indicum L.) - Eny Dyah Yuniwati; Djumali Djumali; Hadi Sudarmo (BUANA SAINS, 2015)
Sesame seed production in rice field one of possible factor is low that needs to be improved. Planting arrangement is expected to increase sesame production. The experiment was conducted in Nganjuk, East Java in April to November 2014. Split Plot Design was used and 3 times replication. The main plot consists two sesame varieties (Winas-1 and Winas-2). Subplot consisted of six plant arrangements, (1) a single row of 50 cm x 25 cm, (2) a single row of 60 cm x 25 cm, (3) double row 40/80 cm x 25 cm, (4) double row 50/80 cm x 25 cm, (5) double row 40/100 cm x 25 cm and (6) double row 50/100 cm x 25 cm. The results showed that the growth, yield components and seed production per hectare of sesame were affected by varieties and plant arrangement. Winas-1 produced a specific leaf weight, leaf area index, leaf relative water content and the number of capsules per plant was higher than Winas-2. Number of branches per plant, weight of 1000 seeds and light interception within and below of shoot were produced Winas-1 lower than Winas-2. Seed production both varieties did not differ. The double row planting arrangement 50/100 cm x 25 cm produced the growth, yield components and seed production per hectare highest and followed by a double row planting arrangement 40/100 cm x 25 cm